Ninhos de Phacellodomus rufifrons (Wied, 1821) (Aves: Furnariidae) como abrigo noturno para uma abelha solitária (Apidae: Centridini) do sudeste do Brasil (Lundiana: International Journal of Biodiversity, 2007)
Sleeping shelters for male Centris (Trachina) fuscata Lepeletier, 1841 (Hymenoptera, Apidae, Centridini) were found in nests of the ovenbird Phacellodomus rufifrons (Wied, 1821) (Furnariidae) in an area of Cerrado (Brazilian savanna), in the state of Minas Gerais, southeastern Brazil, in September 2003. Each day, male bees departed from the shelter early in the morning, returning to them late in the afternoon. Interactions among males were aggressive when two or more males returned simultaneously to the shelter, and lasted until all of them had either occupied a shelter inside the nest stick-matrix or left the nest proximity. Nests occupied by bird families apparently were preferred by bees, as well as those located nearest to a massive food source, a flowering tree Bowdichia virgilioides Kunth, 1823 (Fabaceae). This note emphasizes a very uncommon type of sleeping shelter and its importance for bees.